Implementasi Pembelajaran dengan Kurikulum Merdeka pada Siswa SD Ditinjau dari Teori Konstruktivisme - Putu Lely Somya Prabawati; Ni Ketut Suarni; I Gede Margunayasa (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This study seeks to determine the execution of an independent curriculum during the educational journey in terms for contructivism theory. This category of research involves bibliography, In the data gathering process of this research, two categories of data were collected: primary data and secondary data. Information acquired through research conducted in the library. The methodology employed for data collection is a literature review. The analysis of data in this research employs deductive qualitative analysis techniques.The outcome of the research acquired indicates that implementation of independent curriculum affects the process of learning.This can be observed from the change in the educational journey that offers chances for student for optimize the deepening of concepts and strengthe competencies. The execution of the autonomous curriculum has in impact of strengthening learner's traits or qualities and deepening skills through a knowledge construction process that is in line with constructivism theory.